Linking Neighborhood Context and Health in Community‐Dwelling Older Adults in the Medicare Advantage Program. Issue 6 (12th April 2018) - Jung, Daniel; Kind, Amy; Robert, Stephanie; Buckingham, William; DuGoff, Eva
Abstract : OBJECTIVES: To examine whether neighborhood context moderates the relationship between multiple chronic conditions (MCCs) and function in Medicare Advantage (MA) beneficiaries. DESIGN: Cross‐sectional study. SETTING: Medicare Health Outcome Survey Cohort 16 baseline data from 2013. PARTICIPANTS: MA beneficiaries aged 65 and older (N=187, 434). MEASUREMENTS: We defined disadvantaged neighborhoods as those with an Area Deprivation Index greater than the 85 th percentile. MCCs was defined as having 2 or more chronic conditions. The primary outcome was any self‐reported functional limitations with a basic or instrumental activity of daily living. We used survey‐weighted multivariate linear probability regression to examine whether the neighborhood disadvantage moderates the relationship between MCCs and report of a functional limitation. RESULTS: More than one third (35.6%) of the sample reported a functional limitation. Beneficiaries with MCCs were more likely to report a functional limitation those with 0 or 1 chronic condition (odds ratio (OR)=2.63, 95% confidence interval (CI)=2.50–2.77). Beneficiaries in more‐disadvantaged neighborhoods were more likely to report a functional limitation than those in less‐disadvantaged neighborhoods (OR=1.14, 95% CI=1.08–1.21). In older adults with MCCs, the probability of reporting a functional limitation was 12 percentage points greater in those living in more‐disadvantaged neighborhoods than in those living in less‐disadvantaged neighborhoods. CONCLUSION: Neighborhood context is a significant predictor of functional limitation and moderates the association between chronic conditions and functional limitations. Health plans and public health officials could use publicly available indicators such as the ADI to target interventions to reduce functional impairment.